2020
DOI: 10.1589/jpts.32.7
|View full text |Cite
|
Sign up to set email alerts
|

Neural and visceral manipulation in infants with congenital muscular torticollis: a feasibility study

Abstract: As an alternative to manual stretching, the aim of this study was to investigate the feasibility of using neural/visceral manipulation as a safe and effective intervention to increase neck range of motion of infants with congenital muscular torticollis. [Participants and Methods] Ten 4-month old infants with congenital muscular torticollis received eight sessions of neural/visceral manipulation administered for 30-50 minutes without observed pain. Specific palpation techniques addressed restricted tissue areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Newer evidence supports that manual techniques, such as TCM massage27,28 and neural and visceral manipulation,32 may be feasible, but further high-quality research is needed to establish efficacy. This is consistent with previous research that demonstrated the feasibility of myokinetic stretching,44 and evidence that a home program and soft tissue mobilization, compared with a home program alone, resulted in improved outcomes after 6 weeks of intervention, but no difference after 12 weeks of intervention or at follow-up 45.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer evidence supports that manual techniques, such as TCM massage27,28 and neural and visceral manipulation,32 may be feasible, but further high-quality research is needed to establish efficacy. This is consistent with previous research that demonstrated the feasibility of myokinetic stretching,44 and evidence that a home program and soft tissue mobilization, compared with a home program alone, resulted in improved outcomes after 6 weeks of intervention, but no difference after 12 weeks of intervention or at follow-up 45.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies informed PT intervention for infants with CMT: 1 SR, 27 2 RCTs, 28,31 1 cohort study, 32 1 retrospective study, 29 and 1 qualitative study on the experiences of parents of infants with CMT. 30…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Treatment approaches for CMT include observation only, physical therapy, neural and visceral manipulation, medicine injection, and surgery [ 17 , 23 , 24 ]. Early intervention for infants with CMT aims to prevent craniofacial deformity, limitations in neck motion, imbalance in muscle strength, and spinal deformity [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The non-conditional logistic regression analysis showed that age at initial physiotherapy session was the only risk factor for the occurrence of MM during physiotherapy in infants with CMT (P < 0.05; Table 5). [17,23,24]. Early intervention for infants with CMT aims to prevent craniofacial deformity, limitations in neck motion, imbalance in muscle strength, and spinal deformity [1,2].…”
Section: Logistic Regression Analysis For Risk Factorsmentioning
confidence: 99%